2018
DOI: 10.1016/j.parint.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel Toxoplasma gondii inhibitor chemotypes

Abstract: We profiled three novel T. gondii inhibitors identified from an antimalarial phenotypic high throughput screen (HTS) campaign: styryl 4-oxo-1,3-benzoxazin-4-one KG3, tetrahydrobenzo[b]pyran KG7, and benzoquinone hydrazone KG8. These compounds inhibit T. gondii in vitro with IC values ranging from 0.3 to 2μM, comparable to that of 0.25 to 1.5μM for the control drug pyrimethamine. KG3 had no measurable cytotoxicity against five mammalian cell lines, whereas KG7 and KG8 inhibited the growth of 2 of 5 cell lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“… Derivatives of KG8 ( Sanford et al, 2018 1 ) that were identified as effective in the preliminary screen ( Table 1 ) were further screened for possible cell viability inhibition in NR-9456, U2OS, and HEK293. Potential point mutagenicity was also screened for with the use of a bacterial reversion assay (Ames Assay).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Derivatives of KG8 ( Sanford et al, 2018 1 ) that were identified as effective in the preliminary screen ( Table 1 ) were further screened for possible cell viability inhibition in NR-9456, U2OS, and HEK293. Potential point mutagenicity was also screened for with the use of a bacterial reversion assay (Ames Assay).…”
Section: Resultsmentioning
confidence: 99%
“… Derivatives of KG8 ( Sanford et al, 2018 1 ) that were identified as effective in the preliminary screen ( Table 1 ) were further screened for possible cell viability inhibition in NR-9456, U2OS, and HEK293. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations